Clinical and treatment characteristics of secondary bladder malignancies following low dose rate brachytherapy for prostate cancer - Chin, Chih Peng; Smith, William H.; Cesaretti, Jamie; Terk, Mitchell; Garden, Evan B.; Araya, Joseph Sewell; Palese, Michael A.; Stock, Richard G; Buckstein, Michael (Urologic oncology, 2023)
•Postprostate brachytherapy bladder cancers (BC) present with aggressive pathology.•Postbrachytherapy BC and postprostate cancer BC have similar 5-year overall survival and cancer-specific survival.•Radical cystoprostectomies are effective in treating postbrachytherapy muscle-invasive bladder cancer. To characterize the clinical course and prognosis of bladder malignancies associated with prior prostate brachytherapy We queried our institutional database for patients with bladder cancer (BC) diagnosed between January 2005 and April 2019 who had previously undergone low dose rate (LDR) prostate brachytherapy. Patients diagnosed with BC at least 1 year following LDR prostate brachytherapy with or without external beam radiation therapy were included. Clinical and disease-specific characteristics were abstracted from chart review and survival outcomes were estimated using Kaplan-Meier estimates. We compared the pathologic characteristics and prognosis of secondary BCs in our study cohort to those of BCs diagnosed after prostate cancer managed without radiation reported by the Surveillance, Epidemiology, and End Results (SEER) populational database from 2005 to 2018. Three hundred seventy-five patients were identified with combined diagnosis of prostate cancer and BC, 51 of whom met inclusion criteria in the study cohort. Median times from brachytherapy to BC diagnosis for the study and SEER cohort were 9.5 ± 4.5 and 6.3 ± 4.1 years, respectively. Compared to the SEER cohort, significantly greater proportion of BC from the study cohort presented with high-grade (study: 78.4%, SEER: 52.3%, P = 0.0008) and with MIBC (Study BC 35.3%, SEER BC: 17.5%, P = 0.0009). The study and the SEER cohort had similar 5-year overall survival (study: 67.9%, SEER: 58.0%, P = 0.1099), and 5-year cancer-specific survival (study: 81.0%, SEER: 82.8%, P = 0.5559). The 5-year progression-free survival for the study cohort was 43.7% (95% CI: 28.8–57.7). Compared to bladder cancers following prostate cancer managed without radiation, bladder malignancies following prostate LDR brachytherapy present with higher grade and are more likely to be muscle invasive. Despite the aggressive presenting features of postprostate brachytherapy BC, there were no differences in overall and cancer-specific survival between the groups.